Learning By Doing (John Dewey) dalam Pendidikan Agama Islam - Nurhayati, Ria (Prodi Pendidikan Agama Islam IAINU Kebumen, 2025)
Not only oriented towards worldly welfare, but Islamic education also aims to achieve welfare in the Hereafter. To be able to understand both of these guidelines, humans need to undergo a learning process in formal, informal, and non-formal institutions. One important aspect in the implementation of Islamic education is the methods and models of learning, where educators consider, among other things, philosophical theories. The research is a library study that examines books and scientific articles related to the writing theme. This article discusses how the philosophy of Pragmatism developed by John Dewey has given rise to the Learning by Doing teaching model. Related to Islamic Religious Education, in order for students to gain learning experiences, one of the teaching methods that can be applied is Learning by Doing. This method aims for students to gain experience through direct practice so that learning becomes more meaningful and the values of Islamic teachings can be well internalized by the students.